Extra-pair Paternity in Relation to Age of the Red-breasted Flycatcher Ficedula Parva males. (May 2014) - Mitrus, Joanna; Mitrus, Cezary; Rutkowski, Robert; Sikora, Magdalena
Despite advances in knowledge, in many bird species, the true mating system is unknown, and especially so for birds breeding at low densities under natural conditions. We studied paternity at the population and breeding pair level in the Red-breasted Flycatcher ( Ficedula parva ), a small, migrant passerine breeding in old-growth Białowieża Forest. Over seven breeding seasons we genotyped a total of 159 nestlings and 25 adult males as fathers from 33 broods of the Red-breasted Flycatcher. Extra-pair young were present in eight broods (24.2%). Twelve (7.5%) chicks mismatched with the 'social' male in several loci. Both low breeding density and synchrony in breeding phenology can explain such findings. Also of interest was the share of extra-pair paternity at the individual level, in relation to the age/ornamentation of the extra-pair male. Male Red-breasted Flycatchers exhibit delayed plumage maturation. Young males (second year) are without an orange badge on the throat and breast, while older males (after-second year) are ornamented and have an orange badge. The extra-pair nestlings were found in eight broods, four with young males as a fathers (36.4%) and four in broods of old males (18.2%). However, in all seven cases when the age of the extra-pair partner was known, irrespective of the age of the social father, the extra-pair partner was a male with an orange patch on the breast. This indicated female preference for ornamented males as partners for extra-pair copulation.